An efficient hybrid reconfigurable wind gas turbine power management system using MPPT algorithm - Manjunath T. N.; Mallikarjunaswamy S.; Komala M.; Sharmila N.; Manu K. S. (Institute of Advanced Engineering and Science, 2021)
To improve power management scheme in standalone mode using hybrid wind-gas turbine system. To reduce electrical fluctuations due to permanent magnet synchronous generator (PMSG) in wind turbine system. For power generation, the wind turbine system is a main source. When there is reduction in wind turbine power generation, then gas turbine gets activated immediately and produces the required electricity in effective manner. This reconfigurable power generation system is controlled by perturb and observe maximum power point tracking (P&O_MPPT) algorithm. The proposed wind-gas power management system algorithm and device performance was analysed and simulated using MATLAB R2021a for various wind turbine experiment parameters. The simulation result shows that the proposed model and algorithm effectively meets the load demand when the wind turbine speed falls below the minimum required value.